Robert K. Crane - Na+-Glucose Cotransporter to Cure? - Kirk L Hamilton (Frontiers in Physiology, 2013)
Dr. Robert K. Crane made major contributions to our understanding of carbohydrate metabolism and transport of the intestine over a very long and productive career. This Perspective examines, briefly, his early life and academic positions, but more importantly, this Perspective highlights his contributions to the understanding of coupled Na+-glucose absorption by the small intestine. I discuss how his early hypothesis of a ‘cotransport’ of sodium and glucose ushered in and provided the physiological explanation for the clinical treatment of acute diarrhea and cholera when using oral rehydration therapy (ORT). ORT saves millions of lives each year. Certainly, humankind is better off because of Crane’s hypothesis of the Na+-glucose cotransporter which he put forth over 50 years ago?